Smoking Cessation Rates and Barriers Among Cardiac Patients Following a Cardiac Rehabilitation Programme at a Heart Centre in Malaysia - Chau Chung, Chai; Sing Kock, Bong; Be Kim, Leong; Lin Kiat, Liew; Joanna Varuges, Abraham; Sriganes, Nachimuthu (Hong Kong College of Cardiology, 2025)
Objectives: Smoking cessation is crucial for improving cardiovascular health outcomes in a cardiac rehabilitation programme (CRP). Despite its importance, local studies on smoking cessation rates and barriers among cardiac patients following CRP in Malaysia are limited. This study aimed to evaluate smoking cessation rates and identify barriers to smoking cessation among cardiac patients following CRP at Sarawak Heart Centre, Malaysia.